Review the bamboo-feeding genus Arcofaciella Fennah, 1956 (Hemiptera: Fulgoromorpha: Delphacidae) with description of a new species from India - Li, Hong-Xing; Chen, Xiang-Sheng; Yang, Lin (European Journal of Taxonomy, 2021)
The planthopper genus Arcofaciella Fennah, 1956 (Hemiptera: Fulgoromorpha: Delphacidae) is reviewed. Four species are recognized, of which A. obflexa Guo & Liang, 2005 and A. verrucosa Fennah, 1956 are redescribed, and one new species, A. indiana sp. nov., is described. Habitus photos for adults and illustrations of male genitalia (excluding A. penangensis (Muir, 1919)) are given. A key for identifying the species of Arcofaciella is also provided.